Comparison of the incidence and severity of postoperative sore throat and subglottic airway injury with cylindrical versus tapered cuff endotracheal tubes in women undergoing surgery for breast cancer: a randomized controlled trial - Geng-Ci Chen; Kai-Li Lo; Zhi-Fu Wu; Shun-Ming Chan; Sheng-Yao Cheng; Ching-Lung Ko; Chi-Ming Chu; Wei-Cheng Tseng (BMC Anesthesiology)
Abstract Background Postoperative sore throat (POST) is a minor complication of general anesthesia with tracheal intubation but may negatively affect patient satisfaction and postoperative recovery. The shape of the endotracheal tube (ETT) cuff may influence the incidence and severity of POST. Methods This prospective, randomized, double-blinded study was conducted on 174 female patients with breast cancer. They were randomized into the cylindrical (CYL) (group C) and tapered (TAP) (group T) cuff ETT groups. Data on patient demographics, surgical characteristics, and factors related to tracheal intubation were collected. Furthermore, the incidence and severity of POST at the selected time points were duly recorded for analysis. Other adverse events and anesthesia satisfaction were also documented. Results During the 48-h evaluation period, group T exhibited reduced overall incidence of POST compared with group C. The incidence and severity of POST at 1, 6, 12, 24, and 48 h postoperatively were also significantly lower in group T than in group C. No significant difference in subglottic airway injury was observed between the two groups. Postoperative anesthesia satisfaction was higher in group T. Conclusions The present study demonstrates that the utilization of a TAP cuff ETT rather than a CYL cuff ETT in patients undergoing breast cancer surgery reduced the incidence and severity of POST. The selection of an appropriate ETT for surgical patients could play a pivotal role in alleviating airway complications, enhancing postoperative recovery, and improving anesthesia satisfaction. Trial registration The study was registered at ClinicalTrials.gov (NCT06505850) on 2024-07-17.